Descrição Isoestrutural de duas Chalconas halogenadas - Ludovico, Gabriela Silva (2021)
Chalcones are an important group of organic compounds which have aroused great scientificinterest due to the diverse properties they possess, may have varied biological potentials inaddition to optical properties. Crystallography is a scientific methodology that allows thestructural elucidation of chemical compounds to study their properties, taking into account theexisting relationship between the structure and the properties of molecules this work determinedthe structure of a new chalcone derivative chlorine substituted in compared with a chalconebromo substituted described in the literature, this comparison allowed the understanding of theinfluence of halogens as substituents in chalcones. In this study, crystallographic methods wereused to elucidate the crystal structure of chalcones, the analysis of geometric parameters andsupramolecular arrangement of chalcones shows that the substitution of one halogen for anotherdoes not cause major structural changes, the molecules of this study were shown to beisostructures, that is, have very similar molecular structure.